Main Delay Factors of Implementation EPC Construction Projects in Iraq (Journal of Engineering, 2023)
This essay aims to highlight the most important issues and difficulties facing implementing large projects that follow the turn-key method, considered one of the types of contractual methods in Iraq, especially for large and complex projects requiring speedy completion. The projects implemented in this way face delays and delays in completion, which led to the lack of benefit from the projects for which they were implemented, especially those affecting the lives of citizens within the health sector. The case study dealt with the construction of hospitals with multi-bed capacities within multiple governorates in Iraq, With large financial allocations within the federal budget of the Government of Iraq over several years. After conducting a descriptive statistical analysis of the data obtained through a field survey and interviews with individuals working in the construction sector with experience in their field. The most important 10 factors were identified from a list of 51 delay factors (distributed according to the questionnaire forms) with a high RII. These factors were related to the delay in the payment of the contractor's dues, the delay in processing materials, the issuance of new instructions and regulations, the delay in obtaining official approvals from the relevant authorities, Errors in designs or contracting documents, lack of cooperation between the contracting parties, and multiple spare orders for reasons belonging to the employer. The article also included the most important suggestions that contribute to reducing the delay in completing projects.